Prinsip Partisipasi Dalam Pengadaan Tanah Untuk Kepentingan Umum Terkait Tata Kelola Lingkungan - Arvin Asta Nugraha; I Gusti Ayu Ketut Rachmi Handayani; Fatma Ulfatun Najicha (JURNAL HUKUM DE'RECHTSSTAAT, 2021)
Land Preparation is the activity of providing land by by providing reasonable and fair compensation to the rightful parties. While Environmental Management is an integrated effort in development by paying attention to the environment with structuring, utilization, development, maintenance, recovery, supervision and control of the environment. The approach used in this study is the statute approach. The purpose of this research is to explore the embodiment of the application of the participation principles in land preparation for the public interest in terms of environmental governance and to know clearly the mechanism of land preparation in the implementation of environmental governance. The result of this research is the principle of public participation in the land preparation for the public benefit has a position in environmental governance that is to provide advice and input related to compensation in its implementation in order to be fair and also evenly distributed to parties entitled to compensation.